Implementasi Batu Andesite sebagai Bahan Penyusun Pembuatan Beton pada Fondasi Bored Pile untuk Pembangunan Daerah Aluvial di Semarang Utara - Annisa Wahyu Nur Laily; Sekar Suryaningrum; Ifa Fauziah Maula; Ferina Rahmasari; M. Widan Mudzaky; Laili Nisa; M. Arif Fikri (Jurnal Sains dan Ilmu Terapan, 2024)
The development of the evolutionary environment in urban areas, including Semarang, is influenced by population growth and urbanization. The city of Semarang has two main morphologies: the southern part consisting of hills and the northern part consisting of alluvial coastal plains. Problems that often arise in this area are floods, landslides and land subsidence due to excessive groundwater extraction and compression of alluvial rock. This research aims to overcome the problem of soil movement in North Semarang District by using andesite concrete as the foundation for drilled piles. Andesite stone has high compressive strength and is water resistant, making it ideal as a concrete building material for drilled pile foundations in areas with land subsidence problems. Andesite rock, which is abundant in Central Java, has the advantage of increasing the compressive strength of concrete by 4.21 MPa. This research approach takes the form of a literature review that examines the influence of andesite rock on the compressive strength of concrete and its application as a foundation for drilled embankments.